50th anniversary of the first clinical trial with ICI 46, 474 (tamoxifen): then what happened?. Issue 1 (January 2021) - Jordan, V Craig
Abstract : Following the discovery and approval of the oral contraceptive, the pharmaceutical industry sought new opportunities for the regulation of reproduction. The discovery of the first non-steroidal anti-oestrogen MER25, with antifertility properties in laboratory animals, started a search for 'morning-after pills'. There were multiple options in the 1960s, however, one compound ICI 46, 474 was investigated, but found to induce ovulation in subfertile women. A second option was to treat stage IV breast cancer. Although the patent for ICI 46, 474 was awarded in the early 1960s in the UK and around the world, a patent in the USA was denied on the basis that the claims for breast cancer treatment were not supported by evidence. A trial at the Christie Hospital and Holt Radium Institute in Manchester, published in 1971, showed activity compared with alternatives: high-dose oestrogen or androgen treatment, but the US Patent Office was unswayed until 1985! The future of tamoxifen to be, was in the balance in 1972 but the project went forward as an orphan drug looking for applications and a translational research strategy was needed. Today, tamoxifen is known as the first targeted therapy in cancer with successful applications to treat all stages of breast cancer, male breast cancer, and the first medicine for the reduction of breast cancer incidence in high-risk pre- and post-menopausal women. This is the unlikely story of how an orphan medicine changed medical practice around the world, with millions of women's lives extended.